Preferensi Risiko dan Faktor Yang Memengaruhi Keikutsertaan Asuransi Usahatani Padi (AUTP) di Kabupaten Jember (Jurnal Agribisnis Indonesia, 2022)
The low participation of rice farmers in Jember Regency in crop insurance (asuransi usahatani padi – AUTP) does not mean that rice farmers are risk seeking individuals. The objectives of this study are: (1) to analyze the risk preferences of rice farmers in Jember Regency; (2) analyze the factors that influence the participation of rice farmers in Jember Regency in the AUTP program. The measurement of rice farmer preferences used the multiple price list and constant relative risk averse (CRRA) method; and the analysis of the factors that influenced the participation of rice farmers in the AUTP program used logit regression analysis. The result showed that rice farmers in Jember Regency had a risk preference to avoid risk. The risk preferences of participants farmers of AUTP in Jember Regency are very risk averse; while not participants farmers of AUTP  are risk neutral. The factors that influence the participation of rice farmers in Jember Regency in the AUTP program are: (1) age, (2) rice farming experience, (3) rice farming area, (4) risk preference, (5) AUTP knowledge, and (6) amount of insurance premium that can be paid. The participation of rice farmers in Jember Regency in the AUTP can be increased by increasing farmers knowledge of the scheme and benefits of agricultural insurance through counseling and mentoring.